Anal Neoplasia in Inflammatory Bowel Disease Is Associated With HPV and Perianal Disease. Issue 3 (March 2016) - Ruel, Joannie; Ko, Huaibin Mabel; Roda, Giulia; Patil, Ninad; Zhang, David; Jharap, Bindia; Harpaz, Noam; Colombel, Jean‐Frédéric
Abstract : OBJECTIVES: : Literature describing the risk factors predisposing inflammatory bowel disease (IBD) patients to anal squamous neoplasia is very scarce. Case reports and small case series have implicated perianal Crohn's disease (CD), long‐standing IBD, human papillomavirus (HPV) infection, and immunosuppressive treatment. In this study, we retrospectively examined the association between HPV infection and anal squamous neoplastic lesions among IBD patients from our center. METHODS: : We reviewed the pathology records and slides of IBD patients diagnosed with anal squamous cell carcinomas (SCCs), high‐grade squamous intraepithelial lesions (HSILs), and low‐grade squamous intraepithelial lesions (LSILs) who presented at our center between 1 March 1994 and 9 September 2014. The HPV status of the neoplasms was assessed histologically, by immunohistochemical staining for p16 overexpression, and by global and type‐specific HPV PCR. RESULTS: : SCCs, HSILs, LSILs, and small cell carcinoma were identified, respectively, in six, nine, two, and one IBD patients. All six patients with SCC had CD with perianal involvement. HPV‐related neoplasia was identified in 3/6 cases of SCC (all HPV‐16), 1/1 small cell carcinoma (HPV‐18), and 9/9 HSIL (7 HPV‐16, 2 not typed); 2/2 LSILs were negative for high‐risk HPV. CONCLUSIONS: : In our experience, anal squamous neoplastic lesions in IBD are associated with HPV infection and SCC seem to be associated with perianal CD. Prospective studies are needed to confirm these results.